Proteome Analysis of Potato Starch Reveals the Presence of New Starch Metabolic Proteins as Well as Multiple Protease Inhibitors - Helle, Stanislas; Bray, Fabrice; Verbeke, Jérémy; Devassine, Stéphanie; Courseaux, Adeline; Facon, Maud; Tokarski, Caroline; Rolando, Christian; Szydlowski, Nicolas (Frontiers in Plant Science, 2018)
Starch bound proteins mainly include enzymes from the starch biosynthesis pathway. Recently, new functions in starch molecular assembly or active protein targeting were also proposed for starch associated proteins. The potato genome sequence reveals 77 loci encoding starch metabolizing enzymes with the identification of previously unknown putative isoforms. Here we show by bottom-up proteomics that most of the starch biosynthetic enzymes in potato remain associated with starch even after washing with SDS or protease treatment of the granule surface. Moreover, our study confirmed the presence of PTST1 (Protein Targeting to Starch), ESV1 (Early StarVation1) and LESV (Like ESV), that have recently been identified in Arabidopsis. In addition, we report on the presence of a new isoform of starch synthase, SS6, containing both K-X-G-G-L catalytic motifs. Furthermore, multiple protease inhibitors were also identified that are cleared away from starch by SDS and thermolysin treatments. Our results indicate that SS6 may play a yet uncharacterized function in starch biosynthesis and open new perspectives both in understanding storage starch metabolism as well as breeding improved potato lines.